Lingua del calcio come una lingua settoriale - Szemberska, Anna (AMU Press, 2010)
The main motives of this article involve tecnical terms used by journalists in the Italian football press. The paper presents the Italian of football, its multiple aspects and its characteristics as a special language. The aim of this article, in which we also consider the popularity of football press in Italy, is to analyse its semantic, stylistic, syntactic and textual features.